Dual-Task Training Dan Edukasi Menurunkan Tingkat Risiko Jatuh Pada Lansiadi Pstw Budi Mulia Iv Jakarta Timur - Achwan, Achwan; Utami, Dian; Achirda, Nur (Jurnal Fisioterapi dan Kesehatan Indonesia, 2024)
Fall is an accident that causes injury in elderly. The increased risk of falling in the elderly affects the mobility and independence of the elderly in activity daily living. Interventions for the risk of falling are dual-task training and providing education about the risk of falling. This study aims to determine the effect of a combination of dual-task training and education on the risk of falling in the elderly. This study used a quasi-experimental research design with two groups pre-post test. The sample was selected based on the purposive sampling method with a total sample of 34 people, 17 people in the intervention group were given a combination of dual-task training and education, and 17 people in the control group were given education. The risk of falling is measured using the Timed Up and Go Test (TUGT). The results of the paired sample t-test for the difference in measuring risk of falling before and after in the intervention group obtained p-value=0.000 (p<0.05). The independent sample t-test for the difference between before and after in the intervention group obtained p-value=0.000 (p<0.05). Conclusion from this research there is an effect of dual-task training and education on the elderly in PSTW Budi Mulia IV, East Jakarta.